2019
DOI: 10.1177/0739532919855790
|View full text |Cite
|
Sign up to set email alerts
|

News framing of avian flu: Media advocacy and response to a public health crisis

Abstract: This study explores how South Korean newspapers reported the issue of AI (avian influenza) by employing framing, and the concepts of media advocacy and mobilizing information (MI). Results indicate that news stories were more likely to attribute blame to the government. Government, scientist/researcher, and farmer sources were most prevalent in news coverage. Mentions of tactical MI for the preventive actions increased. Overall, findings indicate the increased media advocacy efforts during repetitive outbreaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
3
15
0
1
Order By: Relevance
“…The research found that the media coverage is intensive and alarmist, especially at the first stage or alarm stage and the third stage or crisis stage, as identified in the research (Vasterman & Ruigrok, 2013). Furthermore, South Korean newspapers frame avian influenza cases with attribution of responsibility by tending to blame on the government (Choi & McKeever, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…The research found that the media coverage is intensive and alarmist, especially at the first stage or alarm stage and the third stage or crisis stage, as identified in the research (Vasterman & Ruigrok, 2013). Furthermore, South Korean newspapers frame avian influenza cases with attribution of responsibility by tending to blame on the government (Choi & McKeever, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…Hardly any media research has been conducted on the intersections of health pandemics and ethnic minorities. Past research on pandemic news coverage primarily focused on mainstream media’s coverage or international news coverage in a cross-cultural context (Choi & McKeever, 2019; Lee, 2014; Oh et al, 2012). Four mainstream U.S. newspapers primarily advanced attribution of responsibility and action frames in its H1N1 pandemic coverage in 2009 (Oh et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Major news frames identified in the past studies on the news coverage of pandemics and health care disparities were attribution of responsibility, consequences, action or solution and statistics (Choi & McKeever, 2019; S.-H. Kim et al, 2010; Oh et al, 2012; Rasmussen, 2014; Shih et al, 2008). Attribution of responsibility frame assigns the responsibility of an event, policy, or issue to individuals or social, political, or economic factors or institutions (S.-H. Kim et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper draws more particular attention to literature on media framing of disease as this paper is about framing MERS in online news coverage. To frame diseases like influenza A(H1N1) (Baum, 2011) Ebola (Kott & Limaye, 2016), HIV/AIDS (Dan, 2018) and avian influenza (Choi & Mckeever, 2019), scholars concluded that the news coverage of disease outbreaks has developed into a standard format, involving three general stages: sounding the alarm, mixed messages, and crisis and containment (Ungar, 2008). Ungar claimed that the media would "shift towards reassuring coverage when they perceived an emerging 'hot crisis'" as the reporting stage starts from the "sounding of the alarm" when "fearful claims making predominates" and ends at the "crisis and containment stage" when the articles seek to undo the alarming risk elements and reassure the public that necessary measures are being taken to mitigate the risk (Ungar, 2008, p. 480).…”
Section: Media Framingmentioning
confidence: 99%